Vacuum-ultraviolet absorption cross-sections of functionalized cyclic hydrocarbons: Five-membered rings. (January 2021) - Christianson, Matthew G.; Doner, Anna C.; Koritzke, Alanna L.; Frandsen, Kelsey; Rotavera, Brandon
Highlights: Quantitative, high-resolution absorption spectra measured in the vacuum-ultraviolet for five-membered cyclic hydrocarbons and oxygenates, the majority of which for the first time. Absorption cross-sections measured for intermediates relevant to combustion chemistry and atmospheric chemistry. Detailed uncertainty analysis calculations conducted. Extensive comparison with literature. Abstract: Cross-sections were measured at 50 °C and 800 Torr using differential absorption spectroscopy in the vacuum-ultraviolet from 5.17 – 9.92 eV for a series of five-membered cyclic hydrocarbons: cyclopentane, cyclopentene, methylcyclopentane, tetrahydrofuran, furan, 2-methyltetrahydrofuran, 2, 3-dihydro-5-methylfuran, tetrahydrofuran-3-one, 2-methyl-1, 3-dioxolane, cyclopentanol, 2-hydroxytetrahydrofuran, cyclopentanone, 2-cyclopenten-1-one, 3-cyclopenten-1-one, 2-methylcyclopentan-1-one, 2-methylcyclopent-2-en-1-one, 1, 2-epoxycyclopentane, 2, 3-epoxycyclopentanone, and 3, 4-epoxycyclopentanone. The majority of the species are functionalized and are directly related to chain-reactions relevant to combustion, such as substituted cyclic ethers and cycloalkenes. Uncertainty calculations were conducted as a function of photon energy to quantify errors associated with experimental repeatability, signal-to-noise ratio, and gas-phase concentration, yielding an upper limit of 5% in spectral regions where absorption is >2%. The primary objective of the present work is to provide quantitative absorption cross-sections of species commonly produced in combustion reactions. Comparing qualitative differences among the five-membered cyclic species, in order to analyze the effect of functional groups on absorption, is a secondary objective. The majority of the spectra are reported for the first time and enable quantitative isomer-resolved speciation measurements in combustion chemistry.